A Novel Multiple Modes Resonant Sensor Featuring Blue Sideband Excitation - Xu, Jiao; Zheng, Zhuoyue; Xi, Jingqian; Zhang, Ziqian; Liu, Huafeng; Zhang, Pan; Chen, Jianlin; Wang, Chen; Kraft, Michael; Wang, Yuan; Martins, R. P.; Mak, Pui-In (IEEE ... Symposium on Mass Storage Systems and Technologies, 2025)
This paper reports a novel MEMS resonant structure functioning as a baseline resonant electrostatic force/temperature sensor, highlighting its substantial potential in sensing applications. The resonator, characterized by a dual-cosine structure, is capable of simultaneous multiple resonant modes actuation within the 300 kHz range, through a sole-source drive approach using the recent emerging Blue Sideband Excitation (BSE) technique. This method enables a distinctive multi-modal response, essential for multi-parameter measurements. The research focuses on the sensor's temperature characteristics, electrostatic perturbation sensitivity, and noise floor. Notably, the study reveals intriguing temperature responses across different modes, where certain modes exhibit a significant frequency rise with increasing temperature, this is counter-intuitive with common MEMS resonator devices, prompting further investigation into the underlying mechanisms. The analysis of electrostatic perturbation sensitivity and noise background further unfolds the resonator's performance under various excitation conditions, laying a foundation for advancing sensor functionality, and providing solid evidence on the viability of the subject. To sum up, this study highlights the resonator's potential as a high-precision sensor, opening new opportunities for MEMS sensor design and multi-parameter measurement applications.